How to Overcome Barriers to Sharing Tacit Knowledge in Non-Profit Organizations? - Oliveira, Márcio (2022)
This paper aims to elaborate a diagnosis and performance matrix concerted on the increment of human capital value by sharing tacit knowledge in non-proft organizations. The following objectives were defned: determine which indicators of tacit knowledge sharing are appliable; determine the measures to be implemented, aiming the augmentation of tacit knowledge sharing and learning organizational. Interviews were conducted with the commanders of volunteer fre brigades in Portugal. It was possible to create a diagnosis and performance matrix to increase the tacit knowledge sharing in these organizations. The application of this matrix improves the tacit knowledge sharing and consequently increases the human capital value. The option of a multiple case research of organizations such as voluntary fre brigades is unique in its action and identity, enabling such organizations with competencies to improve their performance with the purpose of mitigating tragic circumstances that may lead to the loss of human lives.